A Review On Massive Open Online Courses (MOOCs) TVET Design For Lecturers - Raja Rosly, Raja Norhafiza; Hussin, Hanipah; Al-Shami, Samer Ali Hussein; Sidek, S. (Institute Of Advanced Scientific Research, 2018)
The massive open online courses (MOOCs) is very important nowadays. For the past couple of years, MOOCs were a potential medium for education in the context of professional development. MOOCs have been appraised as opportunities for those who are plea for self-improvement especially in education and training. However, little is known about designing MOOCs towards lecturers’ pedagogic knowledge development especially in Malaysian Technical Vocational Education and Training (TVET) context. The purpose of this paper is to review and analyze MOOCs TVET design towards lecturers’ pedagogic knowledge development which is specific to online learning settings in lecturers’ professional development. Content analysis technique was used throughout the research. Focus on online learning setting and professional development framework for online teaching, the analysis revealed several aspects that will be used in the MOOCs TVET design for lecturers’ pedagogic knowledge development. It was showed that there are five aspects; learning activities, learning resource, learning support, interconnected organization and informal reflection to be considered in designing MOOCs TVET for lecturers pedagogic knowledge development. Since MOOCs have been promoted in Malaysia Education Blueprint to globalised online learning and up skilling, therefore in this paper, we have analyzed, reviewed and proposed these five aspects to be considered for designing MOOCs TVET for lecturers’ pedagogic knowledge development.